Intracranial Stenting as Rescue Therapy After Failure of Mechanical Thrombectomy for Basilar Artery Occlusion: Data From the ANGEL-ACT Registry - Gang Luo (Frontiers in Neurology, 2021)
Background and Purpose: Studies on rescue therapy for acute posterior circulation stroke due to basilar artery occlusion (BAO) are limited in the modern era of mechanical thrombectomy (MT). The aim of this study was to evaluate the safety and efficacy of rescue stenting (RS) following MT failure in patients with BAO.Methods: Data were collected from the Endovascular Treatment Key Technique and Emergency Work Flow Improvement of Acute Ischemic Stroke (ANGEL-ACT) prospective registry in China. Patients who underwent MT for BAO with failure of recanalization were enrolled in this study. The patients were divided into the RS and non-RS groups. Clinical and laboratory findings, procedural details, and clinical outcomes were compared between the two groups.Results: Overall, 93 patients with acute BAO were analyzed. The RS group included 81 (87.1%) patients, and the non-RS group included 12 patients. A modified treatment in cerebral infarction (mTICI) score of 2b/3 was achieved in 75 (92.6%) patients in the RS group. Compared with the non-RS group, the RS group had a significantly higher rate of successful recanalization and favorable clinical outcomes (modified Rankin Scale score at 90 days post-procedure, 0–3: 16.7 vs. 51.9%, respectively; P = 0.023) without an increase in the rate of symptomatic intracranial hemorrhage and a significantly lower mortality rate (58.3 vs. 18.5%, respectively; P = 0.006). Furthermore, the use of a glycoprotein IIb/IIIa inhibitor improved the rate of recanalization of the target artery without increasing the rate of symptomatic intracranial hemorrhage.Conclusions: Permanent stenting appears to be a feasible rescue modality when MT fails and might provide functional benefits in patients with acute ischemic stroke due to BAO.